Profitability Of Price, Earnings And Revenue Momentum Strategies: The Indian Evidence - Sehgal, Sanjay; Jain, Kanu (Asian Academy of Management (AAM), 2015)
Momentum has remained an unsettled anomaly in finance. In this paper, we examine the profitability of univariate and multivariate sorted momentum strategies based on prior returns, earnings surprises and revenue surprises using the data for 493 companies that form part of Bombay Stock Exchange (BSE) 500 index in India from January 2002 to June 2010. Momentum profits are found to be persistent in the intermediate horizon (up to six months). Price momentum winners provide higher returns vis-à-vis earnings and revenue momentum winners. On long-short basis, earnings momentum strategy is most profitable. Earnings momentum is able to subsume price and revenue momentum. Further, the informational content of revenue surprises is incrementally very small. Triple sorted momentum portfolio using all the three criteria provides the highest return of 2.28% per month. The Capital Asset Pricing Model (CAPM) and the Fama-French model fail to explain these returns. The post-holding analysis reveals strong overreaction patterns for both winners as well as losers, thus, supporting the behavioural explanation. Momentum winners and losers perform better during market upturns. This study contributes to the asset pricing and behavioral finance literature especially for emerging markets such as India.